Acceleration of acid gel formation by high intensity ultrasound is linked to whey protein denaturation and formation of functional milk fat globule-protein complexes. (August 2019) - Gregersen, Sandra Beyer; Wiking, Lars; Hammershøj, Marianne
Abstract: Ultrasonic homogenization of full fat milk is known to provide changes in the acid-induced gelation behavior, in terms of acceleration of gel formation and increased gel strength. In this study, the dependency of this behavior on ultrasonic power level and treatment temperature was illustrated using an ultrasonic flow cell system, which minimizes temperature increase during treatment. Gel formation was studied by acidification with glucone-δ-lactone at 30 °C using small deformation rheology and effects of ultrasonication on whey protein denaturation, milk fat globule size distribution and proteins associated with the milk fat globule membrane were evaluated. Results illustrate how increased acid-gel strength upon ultrasonication, partly, was attributed to denaturation of whey proteins, but also indicate that changes in the milk fat globule membrane, in terms of increased association of caseins with the milk fat globule membrane, can be of importance by facilitating the formation of highly functional milk fat globule/protein complexes. Highlights: Ultrasound treatment of milk changes the acid-induced gelation behavior. Temperature and power level was shown to be of importance. Effects was linked to denaturation and shift in milk fat globule membrane proteins.